2023
DOI: 10.3390/ijms24032682
|View full text |Cite
|
Sign up to set email alerts
|

PTCHD1 Binds Cholesterol but Not Sonic Hedgehog, Suggesting a Distinct Cellular Function

Abstract: Deleterious mutations in the X-linked Patched domain-containing 1 (PTCHD1) gene may account for up to 1% of autism cases. Despite this, the PTCHD1 protein remains poorly understood. Structural similarities to Patched family proteins point to a role in sterol transport, but this hypothesis has not been verified experimentally. Additionally, PTCHD1 has been suggested to be involved in Hedgehog signalling, but thus far, the experimental results have been conflicting. To enable a variety of biochemical and structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…PTCHD1 is an 888-amino acid, 12-pass transmembrane protein containing a sterol sensing domain (SSD) composed of TM 2–6 and a sterol sensing-like domain consisting of TM7-12 followed by a C terminal tail containing 52 terminal tail containing a PDZ-binding motif. Additionally, two large ectodomains (ECDs) are inserted between TM1 and TM2 and TM7 and TM8 ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTCHD1 is an 888-amino acid, 12-pass transmembrane protein containing a sterol sensing domain (SSD) composed of TM 2–6 and a sterol sensing-like domain consisting of TM7-12 followed by a C terminal tail containing 52 terminal tail containing a PDZ-binding motif. Additionally, two large ectodomains (ECDs) are inserted between TM1 and TM2 and TM7 and TM8 ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hh is one of the key signaling pathways involved in the formation of the neural tube and brain ( 7 ) and in the post-natal brain, it plays a key role in controlling neuronal precursor proliferation in the developing cerebellum and developing dentate granule cells and adult neural precursors. For this reason, while in the past it has been hypothesized as a possible contribution of the gene to the sonic hedgehog (Shh) signaling and synapse formation ( 8 , 9 ), recent studies have demonstrated that, unlike PTCH1, PTCHD1 ectodomains do not bind Shh but a series of RNA binding proteins involved in stress granule and ribonucleoprotein granule assembly ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…PTCHD1 demonstrates 21.62% and 20.65% sequence homology with the Patched domain-containing proteins Patched-1 (PTCH1) and Patched-2 (PTCH2) 7 , respectively, both of which are transmembrane receptors that negatively regulate the Hedgehog (Hh) signaling pathway 12 . Despite this homology, several studies have reported that PTCHD1 does not appear to be similarly involved in repressing Hh-dependent signaling 9,13,14 . Likewise, PTCHD1 also exhibits 21.17% sequence homology with the cholesteroltrafficking transmembrane protein Niemann-Pick disease type C1 (NPC1) 7 , and has correspondingly been observed to directly bind cholesterol 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite this homology, several studies have reported that PTCHD1 does not appear to be similarly involved in repressing Hh-dependent signaling 9,13,14 . Likewise, PTCHD1 also exhibits 21.17% sequence homology with the cholesteroltrafficking transmembrane protein Niemann-Pick disease type C1 (NPC1) 7 , and has correspondingly been observed to directly bind cholesterol 14 . Finally, numerous protein-protein interactions (PPIs) involving the C-terminal PDZ-binding domain of PTCHD1 have been reported, including proteins within both the postsynaptic density (PSD) and the retromer complex 9,13 , potentially indicating a synaptic function of PTCHD1.…”
Section: Introductionmentioning
confidence: 99%